REFLEKSI KRITIS KONDISI DEMOGRAFI INDONESIA: ANTARA BONUS DAN BENCANA DEMOGRAFI - Sarmita, I Made (Media Komunikasi Geografi, 2017)
Indonesia still has various demographic problems. Large population, low population quality, and uneven distribution of population. In quantity, Indonesia can be said will soon enjoy the demographic dividend because the large number of population is a productive age. But the large number of productive age population was not followed by a reliable quality and this can actually be a demographic disaster. This article presents the outlook as a critical reflection of Indonesia's current demographic condition derived from the review of demographic data and related writings. The results obtained are that the demographic conditions of Indonesia are in the "crossroads".  In terms of quantity, Indonesia will enjoy demographic dividend, but in terms of the quality of Indonesia will be faced with the demographic disaster. To avoid the negative impacts of the demographic conditions and to enjoy the momentum, extra effort needs to be done not only by the government, but by all components of the nation. Real, immediate and continuous efforts that can be done include improving the quality of human resources, especially through education and health, creating jobs by all parties, placing the elderly population as an asset, and consolidating the agricultural sector through the empowerment of local farmers as well as cutting wages between agriculture and non-agricultural sectors.